Engaging Students in a Genre-Based Digital Storytelling Project - Rohayati, Saptiwi (Faculty of Tarbiyah and Teacher Training, IAIN Jember, 2020)
Engaging and motivating students are two of the critical factors in a successful learning process. Therefore, teachers are required to seek suitable strategies for achieving learning outcomes. The development of technology in this digital era brings new opportunities for teachers and learners. Technology can be used to support the teaching learning process, particularly for engaging the students in the learning phases. This classroom action research is conducted to find out whether the Digital Storytelling Project helps students to be engaged in the learning process. The participants of the research were tenth-grade senior high school students. The data were collected by using observation, interview, document analysis, peer discussion, and questionnaire. The qualitative content analysis was used for evaluating the obtained data. The finding showed that the students were actively engaged when a digital storytelling project was implemented, especially in selecting digital images and jointly generating ideas of the story. The findings from the classroom observation and interviews also exemplifies the potential use of digital storytelling in helping the students develop ideas and enhance their content knowledge and literacy. Hence, the finding of this research above can be a foundation to claim that the implementation of a digital storytelling project is useful to engage the students in the learning process.